Coronary sinus reductor – a novel approach in “no-option” patients - M. Wańczura, Piotr; Stecko, Wojciech; Curzytek, Andrzej; Wojakowski, Wojciech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Despite the progress that has been made in the treatment of coronary heart disease, there is still a group of patients (approx. 2–3%) whose angina symptoms persist in spite of an optimal therapy (refractory angina, no-option angina). The concept of increasing blood flow to the ischaemic myocardium through revascularization procedures (percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG)) is the gold standard of the treatment. The development of cardiosurgical methods and percutaneous recanalization techniques, as well as the extension of standard pharmacotherapy, allowed a further reduction of symptoms only in some patients. For those symptomatic patients a coronary sinus flow reducer may be a solution [1]. The essence of its action assumes that the obstruction of the blood outflow from the coronary sinus causes an increase in pressure in the venous part of the coronary circulation and in the microcirculation, and facilitates the delivery of oxygen to myocardial cells. An indication for an implantation of the reducer is refractory angina, defined as the persistence of symptoms for more than 3 months despite the combination of pharmacotherapy, angioplasty, and CABG (class II b). These criteria were met by a 70-year-old patient with obesity (BMI = 45.66 kg/m2), hypertension, hyperlipidaemia, type 2 diabetes, after a stroke, CABG, multiple PCI, and pacemaker implantation. The patient was made to use nitroglycerin up to 20 times a day in the period preceding the treatment. Due to the exhaustion of therapeutic options (no possibility of further revascularization of the coronary arteries), the patient was qualified for implantation of a sinus-coronary flow reducer.